Table of Contents. Issue 280 (19th December 2012) - Unknown
Abstract: Thrive in 2013: Assess the health of your organization 2012 #GivingTuesday donations skyrocket Research Blackbaud report provides insight into donor's likes and dislikes Conferences/Events AMI conference educates future leaders CPA nonprofit conference convenes in Mass. San Diego hosts social work/research conference Institute's conference focuses on governance issues Benefits Single provider 403(b) plan reduces costs and heartache, clarifies responsibilities Volunteers New online tool launched to increase impact of pro bono volunteer services Resources Tech Museum of Innovation's Tech Awards Food service book updated for health care providers ING Unsung Heroes awards Millennial authors' book offers insight into their generation and the workplace Employment Law Showing similar incidents of more favorable treatment is essential A reasonable accommodation cannot be summarily withdrawn Examples of retaliation are insufficient Quick Looks Nonprofits faced sluggish contributions in 2012 Childhood obesity initiative obtains $1.5M grant MasterCard, Talloires launch youth job prep program